SELF DISCLOSURE MUSLIMAH BERCADAR DI DESA LUMARING KABUPATEN LUWU (Fakultas Dakwah dan Komunikasi, 2020)
This study aims to determine (1) describing self disclosure of veiled Muslim women in Lumaring Village, Luwu Regency (2) identify and explain acceptance of veiled Muslim women in Lumaring Village, Luwu Regency. This research uses a qualitative approach with a phenomenological research method. Data collection techniques carried out by in-depth interviews with nine informants, five informants who use veils and four informants do not use veils. Data management and analysis techniques using the Huberman and Miles models. The results showed that